Moral hazard with excess returns - Matthias Blonski; Ulf von Lilienfeld-Toal (Mathematics and Financial Economics, 2023)
We consider a public firm characterized by a moral hazard problem. A distinguished player is a CEO or activist shareholder who (i) is unrestricted to trade shares and (ii) has discretion to increase the value of this firm by exerting costly effort. von Lilienfeld-Toal and Rünzi (J Finance 69(3):1013–1050, 2014) investigate and confirm the empirical relevance of both these properties. This article shows that a distinguished player cannot be "priced in" correctly. In particular, such a firm is traded at a discount below its equilibrium value in a market equilibrium. Buyers can systematically earn excess returns on their investment. This prediction is indeed consistent with substantial positive abnormal returns for distinguished player firms within the S &P500 and S &P1500 sample reported in von Lilienfeld-Toal and Rünzi (J Finance 69(3):1013–1050, 2014).
Keywords: G12; G32; C72; D43; D46; 330; Moral hazard; Discretion; Excess returns; Corporate finance; Asset pricing with large shareholders